Magnetization of La(2-x)Sr(x)NiO(4+ delta) (0 < x < 0.5) and observation of novel memory effects - Freeman, P; Boothroyd, A; Prabhakaran, D; Lorenzana, J (2005)
We have studied the magnetization of a series of spin-charge ordered La(2-x)Sr(x)NiO(4+delta) single crystals with 0 < x < 0.5. For fields applied parallel to the ab plane there is a large irreversibility below a temperature T(F1) ~ 50 K and a smaller irreversibility that persists up to near the charge ordering temperature. We observed a novel memory effect in the thermo-remnant magnetization across the entire doping range. We found that these materials retain a memory of the temperature at which an external field was removed, and that there is a pronounced increase in the thermo-remnant magnetization when the system is warmed through a spin reorientation transition.